An Efficient and Practical Method for Olefin Dihydroxylation - Luo, Zhi-bin; Zhao, Chen; Xie, Jimin; Lu, Hong-fei (Synthesis, 2016)
An efficient and economic procedure was developed for the dihydroxylation of various olefin derivatives with commercial KMnO4 as the oxidant in the presence of a quaternary ammonium salt. This practical procedure is suitable for large-scale production of cis-dihydroxy compounds, even those bearing primary and secondary alcohol groups, without overoxidation.
Keywords: dihydroxylation; diols; acrylates; alkenes; potassium permanganate; quaternary ammonium salts